El sur de la península Ibérica y el Mediterráneo occidental : relaciones culturales en la segunda mitad del II milenio a.C. - Garrido Anguita, Juan Manuel, (Archaeopress Publishing Ltd, 2017)
Greek epics are the basis for the first speculations that link societies all along the Mediterranean coast. This work strives to distinguish reality from myth in the pursuit of a bond of certainty between the data provided by historical, literary and archaeological sources.